The effect of Previewing Strategy on Reading Comprehension of Tenth Grade Students at SMK Darul Anwar Singojuruh in Academic Years 2019/2020 - Agus Sulamto; Wageyono; Abdul Halim (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2020)
The objective of the research is to know whether the students taught by using Previewing Strategy get better reading comprehension in descriptive text score, because the observation showed that students have low score reading comprehension in descriptive text. The research design of this research was pre-experimental desaign. The respondents of this research were the tenth grade students of AK class at SMK Darul Anwar, that consisting of 31 students. To collect the data the researcher uses test as the instrument. The data were collected through multiple chioce. The test is given before and after the treatment. The treatment is using Previewing Strategy as a media in teaching and learning reading comprehension descriptive text.The computation result of t-test is 10.66. The result of computation value is consulted to the